A low power portable bioelectronics holter monitor for arrhythmias detection - B - Soh, Charlie Zhan Yi. (2013)
Standard Electrocardiogram (ECG), only records the patient’s heart electrical activity for a short duration and the patients are not encouraged to move throughout the recording process. However, abnormality may not occur during this period. Therefore, there is a need for a portable ECG device, also known as Holter monitor, which provides good accuracy and comfort, to record ECG while patient is carrying out daily activities.